Karakteristik Jemaat Mula-Mula Dalam Kitab Kisah Para Rasul 2: 41-6:7 Dan Relevansinya Terhadap Pertumbuhan Gereja Masa Kini - Rano Surita (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2019)
The condition of God's church today is quite interesting to the author's attention, especially in terms of the character of church growth. The church lost a Biblical figure in terms of church growth. As a result of losing this figure, the church uses any means or justifies any means to force its growth so that they are trapped in unbiblical practices in their growth. The church's indiscretion in observing the Bible to find a good portrait of church growth. As a result of the church's inaccuracy in observing the truth of the Bible, there is a narrowing of the church's understanding of its duties and responsibilities. The understanding of the church in terms of the theology of church growth is an unbiblical theology. This happens because of an incomprehensible understanding of Bible truth, so there are Biblical theological deviations. There are many more shifts in the value of church growth that are happening today, the author is sure that such a method has never existed in the Bible. Too many of God's churches have grown using patterns that are still relevant today and are very Biblical. This is done because church leaders are individuals who have matured in formation and preparation either in science (formal education) or in life experience. Biblical patterns of church growth are still relevant today, as history has proven it.